The Use of the Mind Mapping Method to Overcome Problems in Student Learning Outcomes in Science Subjects in Elementary Schools - Siti nur Rohmah; Honest Ummi Kaltsum (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
Learning methods that are less attractive to students can result in unsatisfactory student learning outcomes. This study aims to analyze the use of mind mapping in addressing the learning outcomes of elementary school students. This study uses a descriptive qualitative research method. This type of research is a case study in which data are obtained from interviews, observation, and documentation. Test the validity of the data in this study using triangulation techniques. The data analysis technique in this study uses an interactive model through data collection, data reduction, and conclusion. The mind mapping method in overcoming problems in learning outcomes is very effective. Because in the interviews, the children before the teacher applied the mind mapping method and after the teacher applied the mind mapping method were very visible. Children are more enthusiastic in the teaching and learning process. Before the teacher applies this method, the child experiences a saturation cycle, resulting in unsatisfactory student learning outcomes. Children's understanding of the material taught using the mind mapping method has increased behavior. The learning atmosphere for children is fun because the mind-mapping method frees children to learn while playing and drawing.